Análise dos otólitos Sagittae de Athrinella brasiliensis (QUOY & GAIMARD, 1825) em estuários com diferentes gradientes de salinidade no Nordeste do Brasil - Clark, Fernando José König (2018)
The inner ear of teleostean fishes has internally hair cells which in contact with otoliths is responsible for orientation and balance and hearing, providing positioning and movement senses. The semicircular canals house the three otoliths suspended in liquid, connected to the optical membranes, being sagittae, used as chronological structure because they are not reabsorbed after their formation by the deposition of calcium carbonate, creating rings making the analysis of this structure on studies of aging and the use of the habitats in which they pass part of their life cycle. Dependent on genetic and environmental factors, the otolith forms are species specific, thus functioning as markers of both the different environmental conditions the fish are subjected to and the characteristic phylogenetic patterns found in the families to which each species belongs. For this, estuaries are important coastal environments for the initial stages of fish life, which provide them with better feeding conditions. However, fish are submitted to environmental factors governed in part by hydrological conditions, which influence salinity, temperature, turbidity and primary productivity. Therefore, the study of t he shape of otoliths is useful for the identification of Atherinella brasiliensis populations, a species with wide distribution in shallow water environments of the Brazilian coast, forming large schools, and important for the beginning of the trophic chains. Considering this, it was sought to understand how the development of otoliths in two distinct environments, mainly in relation to the salinity gradient, and between the juvenile and adult phases, comparing the populations of these environments and thus seeking a better ecological understanding for future projects. management. A total of 1,190 individuals (3,357 g) were captured, distributed between 633 to the Mamanguape estuary and 457 to the Tubarão estuary. The sagittae otoliths presented a general elliptic, concave-convex shape. The morphometric parameters were higher for the upper zones of the studied environments. The indices of ellipticity and shape factor were higher in the upper estuary and in the hypersaline estuary, and differences were observed only for juveniles and adults, with circularity and rectangular indexes being higher among juveniles.